2020
DOI: 10.3390/ijms21218059
|View full text |Cite
|
Sign up to set email alerts
|

7-HYB, a Phenolic Compound Isolated from Myristica fragrans Houtt Increases Cell Migration, Osteoblast Differentiation, and Mineralization through BMP2 and β-catenin Signaling

Abstract: The seeds (nutmegs) of Myristica fragrans Houtt have been used as popular spices and traditional medicine to treat a variety of diseases. A phenolic compound, ((7S)-8′-(benzo[3′,4′]dioxol-1′-yl)-7-hydroxypropyl)benzene-2,4-diol (7-HYB) was isolated from the seeds of M. fragrans. This study aimed to investigate the anabolic effects of 7-HYB in osteogenesis and bone mineralization. In the present study, 7-HYB promotes the early and late differentiation of MC3T3-E1 preosteoblasts. 7-HYB also elevated cell migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…Therefore, research targeting osteoblasts is necessary for the development of anabolic drugs [18,25,26]. Recently, our group demonstrated the biological activities and mechanisms of natural compounds in osteoblasts [27][28][29][30][31]. In the present study, we demonstrated the novel function of PASI isolated from P. suffruticosa in pre-osteoblasts.…”
Section: Discussionsupporting
confidence: 57%
“…Therefore, research targeting osteoblasts is necessary for the development of anabolic drugs [18,25,26]. Recently, our group demonstrated the biological activities and mechanisms of natural compounds in osteoblasts [27][28][29][30][31]. In the present study, we demonstrated the novel function of PASI isolated from P. suffruticosa in pre-osteoblasts.…”
Section: Discussionsupporting
confidence: 57%
“…Immunofluorescence was performed as previously described [ 49 ]. Cells were fixed for 10 min at room temperature, permeabilized with 0.2% Triton X-100 in 1× PBS for 20 min, and blocked with 3% BSA diluted in 1× PBS for 1 h. The cells were incubated with anti-RUNX2 primary antibody (1:200, Cell Signaling Technology, Beverly, MA, USA) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed as previously described [ 53 ]. Cells were fixed, permeabilized, and blocked with 3% BSA diluted in 1 × PBS for 1 h. The cells were incubated with an anti-RUNX2 antibody (1:200, Cell Signaling Technology, Beverly, MA, USA) overnight at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Immunofluorescence was performed as previously described [53]. Cells were fixed, permeabilized, and blocked with 3% BSA diluted in 1 × PBS for 1 h. The cells were incubated with an anti-RUNX2 antibody (1:200, Cell Signaling Technology, Beverly, MA, USA) overnight at 4 • C. After washing three times in 1 × PBS, the cells were incubated with an Alexa-Fluor 568-conjugated secondary antibody (1:500, Invitrogen, Carlsbad, CA, USA) for 2 h at room temperature, stained with DAPI (Sigma-Aldrich, St. Louis, MO, USA), washed three times, mounted on glass slides, and observed using a confocal microscope (K1-Fluo Confocal Laser Scanning Microscope, Korea).…”
Section: Immunofluorescencementioning
confidence: 99%